2016
DOI: 10.1117/12.2223909
|View full text |Cite
|
Sign up to set email alerts
|

Experimental effects on IR reflectance spectra: particle size and morphology

Abstract: For geologic and extraterrestrial samples it is known that both particle size and morphology can have strong effects on a species' infrared reflectance spectra. Due to such effects, the reflectance spectra cannot be predicted from the absorption coefficients alone. This is because reflectance is both a surface as well as a bulk phenomenon, incorporating both dispersion as well as absorption effects. The same spectral feature can even be observed as either a maximum or minimum. The complex effects depend on par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…While this paper does not explicitly focus on particle size effects, one must bear in mind that such effects can strongly influence spectral manifestation and therefore the spectral analysis. 22,46,48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this paper does not explicitly focus on particle size effects, one must bear in mind that such effects can strongly influence spectral manifestation and therefore the spectral analysis. 22,46,48…”
Section: Resultsmentioning
confidence: 99%
“…While this paper does not explicitly focus on particle size effects, one must bear in mind that such effects can strongly influence spectral manifestation and therefore the spectral analysis. 22,46,48 The interferent materials used in this study contain chemical compositions that are commonly found in the natural environment, i.e., in good abundance on the earth's surface. In Fig.…”
Section: Hemispherical Reflectance Data Of Pure and Mineral Mixtures mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the same chemical can exhibit vastly different spectra, or "signatures," depending on the size of particles composing the deposit. 3,4 There is strong interest in understanding the impact of morphology on such chemical signatures, and in developing reflectance models which can compute signatures displaying behavior consistent with observed dependencies. Here we present such a model, which leverages computational tools developed within the planetary and atmospheric science communities for evaluating the scattering and extinction properties of individual particles based on their size and shape, and the complex refractive index n+ik of the material itself.…”
Section: Introductionmentioning
confidence: 92%
“…The reduction in particle size increases the inter particle boundaries and therefore the number of reflections at the boundaries increases. Thus, reflectivity increases at most of the wavelengths when the particle size decrease 23,24 .…”
Section: Implications Of Nano-structurementioning
confidence: 98%